Are women having a vaginal birth after a previous caesarean delivery at increased risk of anal sphincter injury?. (13th March 2014) - Hehir, MP; Fitzpatrick, M; Cassidy, M; Murphy, M; O'Herlihy, C
<x xml:space="preserve">Abstract</x> Objective To examine the incidence of obstetric anal sphincter injury in women who had a successful vaginal birth after a previous caesarean delivery (VBAC). Design Retrospective analysis of prospectively gathered data. Setting A tertiary referral university institution. Population All secundiparous women with a previous caesarean delivery who had a VBAC from 2001 to 2011. Methods Details of maternal demographics, intrapartum characteristics and outcomes were examined in cases of VBAC with accompanying anal sphincter injury. Main outcome measures Rates of obstetric anal sphincter injury and associated risk factors. Results During the study period there were 3071 trials of labour in secundiparous women with a previous caesarean delivery; 65% (1981/3071) of these had a successful VBAC. Women having a VBAC were at greater risk of anal sphincter injury than nulliparous women having a vaginal delivery over the same period (5% [98/1981] versus 3.5% [1216/34 496], P = 0.001, odds ratio 1.4, 95% CI 1.15–1.75). The rate of instrumental delivery in woman having a VBAC was 39% (771/1981). On multiple logistic regression analysis an increased rate of instrumental delivery was a strong predictor of sphincter injury (P = 0.03, odds ratio 1.15, 95% CI 1.01–1.3). When the first labours of women with sphincter injury in the VBAC group were examined, 70% (60/86) had been in labour before undergoing their caesarean delivery. Conclusion The incidence of anal sphincter injury in women undergoing VBAC is 5% and birthweight is the strongest predictor of this. The rate of instrumental delivery in this group was also increased.